THE IMPORTANCE OF TEACHING BIOPHYSICS WITH THE USE OF INTERACTIVE METHODS IN MEDICAL EDUCATION - Z.M.Narzullayeva (TADQIQOTLAR, 2025)
Abstract. This article analyzes the role of biophysics in medical education, its practical significance, its role in forming the competencies necessary for future doctors, and  the  main  directions  of  biophysical  research  methods  in  modern  medicine  and interdependence  of  the  various  processes  occurring  in  the  human  body,  it  is  often possible  to  distinguish  among  them  those  that  are  close  to  physical  processes. For example,  such  complex  physiological  processes  as  blood  circulation  are  actually physical  processes,  since  this  process  is  associated  with  the  flow  of  fluid  - hydrodynamics, the propagation of elastic vibrations along the vessel - vibrations and waves, the mechanical work of the heart - mechanics, the generation of biopotentials - electricity, etc. Breathing is associated with the movement of gases - aerodynamics, heat transfer - thermodynamics, evaporation (spatial transitions), etc. C